Análise do alinhamento da estratégia de marcas próprias do atacado distribuidor em relação às perspectivas dos clientes varejistas - Piato, Éderson Luiz (2011)
For the past few years, wholesalers have shown strong involvement with marketing strategies, including private labels management. This study aims at evaluating the alignment between wholesalers private labels strategy and its retailing customers perspectives, analysing the marketing elements involved in this relationship. This is a qualitative research with exploratory purpose. The research was developed in five sequential phases. In phase one, secondary data was collected though bibliographic research. During phase two, research s elements and questions were defined. Wholesalers were contacted during phase three, asking for retailers contacts from their database (retailers that buy private labels from the wholesalers). During this phase, a pre-test of the study was developed with two different retailers. In phase four, semi-structured interviews with managers and owners of fifteen food retailers in Sao Paulo and Minas Gerais were developed. The interviewed retailers are wholesalers private labels customers. Phase five was characterized by the data analysis, using content analysis and data sources triangulation. As a result, the study presents an analysis of wholesalers private labels strategy based on retailers perspectives about the marketing elements involved in this strategy. Through a comparative analysis of these elements, it was possible to evaluate how retailers understand the marketing elements developed and managed by wholesalers. It was also possible to analyse which aspects facilitate or not the alignment between agents perspectives, as well as strategic and managerial implications of the gaps in this strategy. From the results, it was possible to develop an analytical scheme with suggestions to facilitate the alignment between wholesalers private label strategies and the role of its customers (the interviewed retailers), specially in terms of joint management and implementation of the strategy. Finally, limitations of the research and suggestions for future researches were presented.